EMBRIOLOGI DALAM AL-QUR'AN: KAJIAN PADA PROSES PENCIPTAAN MANUSIA - Kiptiyah, Kiptiyah (ULUL ALBAB Jurnal Studi Islam, 2007)
Researchers have studied human embryology for many centuries, but there's no yet detailed appropriate explanation about the process of human creation: even the told theory sometimes digress from the fact. This caused by the limitation of human science and knowledge.Al-Qur'an explains in detailed how Allah creates human. Allah said in Surat al-Mu'minuun, verse 12-14. Man We did create from a quintessence (of clay); then We placed him as (a drop of) sperm in a place of rest, family fixed; then We made the sperm into a clot of congealed blood; then of that clot We made a (fetus) lump; then We made out of that lump bones and clothed the bones with flesh; then We developed out of it another creature. So blessed be God, the best to create! Thirteen centuries after al-Qur'an released, there were researchers on embryology. The result of those researchers proved the legitimate concepts of embryology in al-Qur'an. Based on those findings, this research's theme is: "Embryology inside al-Qur'an: the study of how human's creation. This research discusses the creation process of the first human (Adam a.s.) and the creation process of humans after based on the embryology concept revealed in al-Qur'an by using integrated science as the approach.